THE ROLE OF PSYCHOLOGICAL CAPITAL AND SUPPORTIVE ORGANIZATIONAL CULTURE ON AUTHENTIC LEADERSHIP: AN EMPIRICAL (Third Sector Social Economic Review, 2016)
The basic characteristics of authentic leadership, which is one of the modern leadership approaches, gives importance to ethical and moral values, to be able to establish transparent relationships and be able to give impartial decision. People are the most valuable asset of the organizations, thus the individuals hope, optimism, self-efficacy beliefs and the development of psychological endurance will have a positive impact on the performance of the organization. Supportive organizational culture allows employees to take risks and initiatives. The personal rights of employees are respected andknowledge is shared. Authentic leadership, psychological capital and supportive organizational culture are combination of variables, which were observed that weren’t seen in our country. It is considered that this study is an important contribution to the scientific literature can be made. In this study, the dimensions of psychological capital and supportive organizational culture on the dimensions of the effects of authentic leadership were evaluated. Descriptive (experimental design) research is anticipated. Research group of the study consists of 2590 persons who work in a public institution in Ankara. Judicial and sampling techniques the data obtained from 262 employees were included in the research A questionnaire consists of 53 questions prepared in advance and the method of instant data (cross-sectional) were collected. The data were analyzed with SPSS statistics 22 and Amos 22 programs. To test the a structural equation model has been built. As a result of research, psychological capital and supportive organizational culturehave have significant effects on authentic leadership.
Keywords: Psychological Capital; Supportive Organizational Culture; Authentic Leadership